Perancangan Sistem Presensi Karyawan Berbasis RFID KTP Dengan Metode Waterfall Pada Trilogiz Printing - Yuyun Purniawan; Aries Saifudin (CV. Multi Kreasi Media, 2024)
In company administration, recording attendance is an important thing to do. A decent attendance system is needed to overcome various problems in the world of work. Recording attendance in a conventional way is no longer considered effective, which requires paper for media and a place for archiving. In addition, various fraud in conducting attendance is also very likely to occur in the conventional attendance system. One company called Trilogiz Printing still uses the system. With problems as mentioned, a feasible and effective attendance system must be created and run in order to solve the above problems. By conducting research using a case study approach, this research is targeted to produce a presence system that can overcome these problems. The software development method chosen is the Waterfall method. One type of attendance that is currently popular is KTP-based RFID, where KTP is a personal identity card which is a medium for attendance with better security than other types of attendance media.